Reflections on Cultural and Linguistic Diversity in a Chinese Australian Community Museum. Issue 1 (2nd January 2021) - Couchman, Sophie
ABSTRACT: The cultural and linguistic heritage of Chinese Australians is complex and often poorly understood by Australian communities. It can be challenging for GLAM sector organisations to both understand and share the complexity of Chinese culture in Australia in a meaningful and coherent way. Using the Chinese Museum in Melbourne, Australia as a case study, this paper reflects on how this diversity shaped the work of the Museum. Drawing on personal experience as the curator of the Museum, the author argues that communities are evolving, our understandings of them imperfect and so learning about cultural complexity is an ongoing iterative process.